A review of the impact of bilingualism on the development of phonemic awareness skills in children with typical speech development. (February 2013) - Wren, Yvonne; Hambly, Helen; Roulstone, Sue
This review investigated what is known about the impact of bilingualism on children's phonemic awareness. Studies of bilingual children where one language was English were identified by searching electronic databases and bibliographies from the last 50 years. Thirteen studies were analysed thematically and summarized in terms of methods and key findings. Findings suggest a variable pattern of performance, with some studies showing no difference between bilingual and monolingual performance on tasks. However, there was also evidence for advanced acquisition of phonemic awareness skills in some bilingual children, mediated by characteristics of languages spoken.